1992
DOI: 10.1021/la00046a015
|View full text |Cite
|
Sign up to set email alerts
|

Concentrated emulsions. 3. Studies on the influence of continuous-phase viscosity, volume fraction, droplet size, and temperature on emulsion viscosity

Abstract: Explosive-type emulsions with internal-phase fractions from 0.74 to 0.92 were studied to quantify the effects of average droplet size, continuous-phase viscosity, volume fraction, and temperature on emulsion viscosity measured at low rates of shear. Plots of emulsion viscosity vs volume fraction of the dispersed phase (0) were obtained at 80 °C for two different emulsions varying in continuous-phase composition, but having constant droplet size profiles. Emulsion viscosity increased steeply as the internal pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 0 publications
2
28
0
Order By: Relevance
“…Apart from the mediating effect of surfactants, the stability of conventional water in oil microemulsions can also be enhanced by increasing the viscosity of the organic phase 59. For the case of pulsed plasma deposited poly(vinylbenzyl chloride), although these films are not sufficiently flexible at room temperature to form emulsions, the plasmachemical layer can be considered to become a highly viscous organic phase at elevated temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the mediating effect of surfactants, the stability of conventional water in oil microemulsions can also be enhanced by increasing the viscosity of the organic phase 59. For the case of pulsed plasma deposited poly(vinylbenzyl chloride), although these films are not sufficiently flexible at room temperature to form emulsions, the plasmachemical layer can be considered to become a highly viscous organic phase at elevated temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely to be caused by the increase in the viscosity and average density of the emulsion templates with increasing internal phase volume. It has been reported that there are several factors affecting the viscosity of emulsions; emulsion viscosity increases with higher internal phase volume and decreasing droplet size[40].…”
mentioning
confidence: 99%
“…Therefore, the internal, dispersed droplets are deformed and take the shape of polyhedra separated only by thin layers of the continuous phase, meaning that, HIP emulsions effectively have a liquid-in-liquid foam type structure [16]. As HIP emulsions are so highly concentrated with tightly packed water droplets, they can have very high viscosities and therefore usually behave more like gels, rather than liquids [17]. Another defining property, which was the basis for the selection of these emulsions for use in this work, is that an emulsion may be made almost entirely from one liquid but exhibit the surface properties of another liquid [16].…”
Section: Introductionmentioning
confidence: 99%